1990
DOI: 10.2105/ajph.80.10.1225
|View full text |Cite
|
Sign up to set email alerts
|

Lyme disease in New Jersey outdoor workers: a statewide survey of seroprevalence and tick exposure.

Abstract: To evaluate the spread of Lyme disease in New Jersey, we conducted a statewide cross-sectional study of Lyme disease seroprevalence in a high-risk occupational group of outdoor employees. Of the 689 employees who participated in the study, 39 (5.7 percent) were positive for antibody to B. burgdorferi, the causative agent of Lyme disease. Seroprevalence varied markedly by county; unexpectedly high seroprevalence rates were found in several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Previous research supports the notion that performance of preventive behaviors reduces the risk of Lyme disease (Goldstein et al, 1990). Perceptions, knowledge, attitudes, and past experiences regarding Lyme disease have been reported to impact the utilization of Lyme disease-prevention measures in various geographic locations but have not systematically been studied for residents of New York State, the state with the largest number of reported cases of Lyme disease.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous research supports the notion that performance of preventive behaviors reduces the risk of Lyme disease (Goldstein et al, 1990). Perceptions, knowledge, attitudes, and past experiences regarding Lyme disease have been reported to impact the utilization of Lyme disease-prevention measures in various geographic locations but have not systematically been studied for residents of New York State, the state with the largest number of reported cases of Lyme disease.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Environmental and personal protection measures influence the risk of tick bites and thus the risk for acquiring Lyme disease (Goldstein et al, 1990). Prevention of tick bites is facilitated by avoidance of tick-infested habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Određivanje grupa ljudi u riziku je bilo predmet istraživanja mnogih epidemioloških studija, a rezultati seroepidemioloških ispitivanja su pokazali da su to šumski radnici, lovci, ribolovci, vojnici, kamperi, rekreativci, stočari, ratari i radnici koji održavaju parkovske površine, što su profesije u kojima je muški pol zastupljeniji. U ovoj studiji je, kao i u brojnim drugim utvrđena veća zastupljenost muške populacije (7,8,9). Pri ubodu, krpelji luče materije koje imaju antikoagulantno, inflamatorno, anestetičko i imunosupresivno dejstvo, na šta će domaćin odreagovati imunološki i alergijski.…”
Section: Diskusijaunclassified
“…Of the 13 articles where "occupation(al)" or "work(er)" appeared, the majority were seroprevalence studies of individuals working in the forestry, parks, land management, and agricultural sectors in various locations around the world (e.g. Cisak, W ojcik-Fatla, Zają c, Sroka, & Dutkiewicz, 2012;Goldstein et al, 1990;Guy, Bateman, Martyn, Heckels, & Lawton, 1989;Nakama, Muramatsu, Uchikawa, & Yamagishi, 1994;Smith et al, 1988;Stanchi & Balague, 1993). One study from the United States reported the results of a survey of workers regarding their knowledge of Lyme disease and their behaviour regarding tick-bite prevention and one article provided a comprehensive review of the occupational risks (Piacentino & Schwartz, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%